The Effect of ESG Score, Dividend Policy, and Profitability on Cumulative Abnormal Return: A Study of Companies in The SRI-KEHATI Index - Reza Saputra; Ranila Suciati Suciati (School of Accountancy, University of Agung Podomoro, 2026)
This study aims to analyze the effect of ESG score, dividend policy, and profitability on Cumulative Abnormal Return (CAR) in companies included in the SRI-KEHATI Index on the Indonesia Stock Exchange for the 2020–2024 period. The research population consists of all issuers in the SRI-KEHATI Index, with a final sample of 94 observations from 30 companies that consistently have ESG score in Refinitiv. Data were obtained through documentation of annual reports and financial statements downloaded from the official websites of the Indonesia Stock Exchange and the respective issuers, supporting financial data from EMIS, and ESG score data from the Refinitiv database, which were then quantitatively analyzed using panel data regression and event study with the assistance of Microsoft Excel 2019 and E-Views 12. The results show that the Environmental Score and Governance Score have a positive and significant effect on CAR, while the Social Score and Dividend Payout Ratio have a negative and significant effect. Profitability measured by ROA does not have a significant effect on CAR, whereas ROE has a positive and significant effect. In addition, the event study results indicate the presence of abnormal returns around the announcement period of the SRI-KEHATI Index composition, which is conducted twice a year, confirming that the market perceives information related to this sustainability index as valuable signals in investment decision-making.